Regulation of locomotion and motoneuron trajectory selection and targeting by the Drosophila homolog of Olig family transcription factors - Oyallon, Justine (Elsevier, 2012)
During the development of locomotion circuits it is essential that motoneurons with distinct subtype identities select the correct trajectories and target muscles. In vertebrates, the generation of motoneurons and myelinating glia depends on Olig2, one of the five Olig family bHLH transcription factors. We investigated the so far unknown function of the single Drosophila homolog Oli. Combining behavioral and genetic approaches, we demonstrate that oli is not required for gliogenesis, but plays pivotal roles in regulating larval and adult locomotion, and axon pathfinding and targeting of embryonic motoneurons. In the embryonic nervous system, Oli is primarily expressed in postmitotic progeny, and in particular, in distinct ventral motoneuron subtypes. oli mediates axonal trajectory selection of these motoneurons within the ventral nerve cord and targeting to specific muscles. Genetic interaction assays suggest that oli acts as part of a conserved transcription factor ensemble including Lim3, Islet and Hb9. Moreover, oli is expressed in postembryonic leg-innervating motoneuron lineages and required in glutamatergic neurons for walking. Finally, over-expression of vertebrate Olig2 partially rescues the walking defects of oli-deficient flies. Thus, our findings reveal a remarkably conserved role of Drosophila Oli and vertebrate family members in regulating motoneuron development, while the steps that require their function differ in detail.